BEARDED PIG - Mohd Azlan, Jayasilan; Sally Soo, Kaicheen (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
The Bearded Pig, Sus barbatus (Fig. 1) is known from Malaysia (the southern Malay Peninsula, Sabah and Sarawak), Brunei Darussalam, Indonesia (Kalimantan and Sumatra), and some of the islands of the Philippines. They are widely distributed from the coastal lowlands, including peat swamps and dipterocarp forests with undulating hills, up to the highlands on Borneo. The pig has a dark brown-grey coat, with a distinct grey ‘beard’ on the lower jaw. It has small eyes and long ears, and its snout ends in a disk-shaped structure with the nostrils. The adult male’s upper canines form a set of tusks. Juveniles have longitudinal stripes that disappear with growth. The Bearded Pig is an omnivore, primarily feeding on fruits, roots, nuts, insects and seeds of Dipterocarpaceae and Fagaceae.